United Against Rabies Forum: The first 2 years - Tidman, Rachel; Fahrion, Anna Sophie; Thumbi, S. M.; Wallace, Ryan M.; De Balogh, Katinka; Iwar, Vivian; Yale, Gowri; Dieuzy-Labaye, Isabelle (Frontiers in Public Health, 2023)
Rabies continues to kill an estimated 59,000 people annually, with up to 99% of human cases transmitted by domestic dogs. The elimination of human deaths from dog-mediated rabies is achievable by applying a One Health approach, and the framework to do this is outlined in Zero by 30: the Global Strategic Plan to end human deaths from dog-mediated rabies by 2030. To build on this global goal, and implement the approaches set out in Zero by 30, the United Against Rabies Forum was launched in 2020. This paper gives a review of the objectives, governance, activities and achievements of the United Against Rabies Forum to date. It also outlines ongoing work, and next steps as the United Against Rabies Forum reviews its first 2 years of activities and identifies priority areas for the coming 12 months.